Causality Analysis Between Unemployment, Poverty, and Economic Growth in the Southern Sumatra Region - Ferdinand Anjas Karo Karo; Yusnida Yusnida (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study aims to look at the relationship between poverty, unemployment, and economic growth in five provinces in the Southern Sumatra region (Sumbagsel) from 2000 to 2022 through the use of time series data. The method used is a quantitative approach using the Granger causality model. The results showed that: (1) there is no causal relationship between unemployment and economic growth or vice versa in the five provinces in Southern Sumatra (Sumbagsel), (2) there is a one-way causal relationship between poverty and economic growth in Bangka Belitung Islands Province, while there is no relationship between economic growth and poverty, (3) there is a causal relationship between poverty and unemployment rate and vice versa in Bangka Belitung Islands Province and South Sumatra, while there is a one-way relationship between poverty and unemployment rate in Lampung Province, and a one-way relationship between unemployment rate and poverty in Jambi Province. However, there is no significant causal relationship in Bengkulu Province, either in the form of a one-way or two-way relationship.